2012
DOI: 10.3354/meps09749
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and colonisation of the western Antarctic Peninsula by the seabird tick Ixodes uriae

Abstract: Recent observations on the western Antarctic Peninsula have suggested that changing climatic conditions may be increasing pressure on breeding seabirds due to higher exploitation rates by the tick Ixodes uriae. Using data from 8 microsatellite markers and ticks from 6 Pygoscelis spp. colonies, we employed a population genetics approach to specifically test the hypothesis that I. uriae is expanding south-westward along the peninsula from the Subantarctic region. Contrary to expectations, tick genetic diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 62 publications
1
36
0
Order By: Relevance
“…Recent development of host races within nesting colonies Dietrich et al (2012aDietrich et al ( ,b, 2013Dietrich et al ( , 2014, Kempf et al (2009a), McCoy et al (1999, McCoy and Tirard (2000), McCoy et al (2001McCoy et al ( , 2003aMcCoy et al ( ,b, 2005bMcCoy et al ( , 2012, McCoy andTirard (2000, 2002) Rhipicephalus annulatus…”
Section: Ixodes Texanusmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent development of host races within nesting colonies Dietrich et al (2012aDietrich et al ( ,b, 2013Dietrich et al ( , 2014, Kempf et al (2009a), McCoy et al (1999, McCoy and Tirard (2000), McCoy et al (2001McCoy et al ( , 2003aMcCoy et al ( ,b, 2005bMcCoy et al ( , 2012, McCoy andTirard (2000, 2002) Rhipicephalus annulatus…”
Section: Ixodes Texanusmentioning
confidence: 98%
“…The exploration of population structure and host race formation in Ixodes uriae is the most comprehensive body of work in tick population genetics (Dietrich et al, , 2014(Dietrich et al, , 2012bKempf et al, 2009a;McCoy et al, 2012McCoy et al, , 1999McCoy et al, , 2005aMcCoy et al, , 2001McCoy et al, , 2003aMcCoy et al, , 2005bMcCoy andTirard, 2000, 2002;McCoy et al, 2003b). This species is part of the I. ricinus complex and a vector of the Lyme disease pathogen, B. burgdorferi.…”
Section: Ixodesmentioning
confidence: 99%
“…After observing asynchrony in the timing of tick exploitation on different sympatric seabird species, McCoy et al (1999) hypothesized that I. uriae populations may consist of a series of local host-specific groups. They tested the predictions of this hypothesis using a population genetic approach with specifically-developed microsatellite markers (McCoy and Tirard, 2000) and found that throughout the different zones of its global distribution, this tick had indeed formed host-specific genetic groups (or host races) and that these host races had evolved independently in different isolated regions (McCoy et al, 2001, 2005, 2012; Dietrich et al, 2012). This divergence has been suggested to be relatively recent (Kempf et al, 2009a), but has been accompanied by both phenotypic changes in body morphology (Dietrich et al, 2013) and host-associated variation in performance on different host species (Dietrich, 2011).…”
Section: Integration Of Population Genetics To Study Host Usementioning
confidence: 99%
“…albatross and shags) when they breed in sympatry (McCoy et al, ), and that life history can influence the level of host specificity and thus dispersal of seabird parasites (Wessels, Matthee, Espinaze, & Matthee, ). However, host specificity was not evident between three penguin species in the western Antarctic Peninsula (McCoy et al, ), nor among two related species of penguin in the Crozet Archipelago (McCoy, Chapuis, et al, ), nor among the two recently split Little Penguin species (this study), suggesting that ticks might readily be shared among penguin species. The present study also suggests—although based on a single specimen—that New Zealand penguin species (Little and yellow‐eyed penguins) may share ticks.…”
Section: Discussionmentioning
confidence: 99%